2023
DOI: 10.1088/1361-6463/acfb8e
|View full text |Cite
|
Sign up to set email alerts
|

How to benchmark triboelectric nanogenerator: a review

Chaojie Chen,
Guoqiang Xu,
Jingjing Fu
et al.

Abstract: Triboelectric nanogenerators (TENGs) can convert random mechanical vibrations around the environment into electricity and have huge potential in artificial intelligence, blue energy, carbon neutrality, human-machine interface, e-skin, etc. Although many efforts have been made on the working mechanism and performance enhancement in the past decade, characterizing and evaluating the performance of TENGs remains challenging due to the lack of benchmarking guidelines. Previous works based on different measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The similar output voltage of the PENG measured before and after shielding the device with a grounded single side conducting layer also demonstrates that the signals are actually piezoelectric outputs of the aerogel PENG. 67–69 The output performance of the anisotropic aerogel-based PENG was also measured by applying force along the transverse direction. The nanogenerator delivered an open-circuit voltage of ∼10.5 V and a short circuit current of ∼54 nA along the transverse direction, which is less than the freezing direction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The similar output voltage of the PENG measured before and after shielding the device with a grounded single side conducting layer also demonstrates that the signals are actually piezoelectric outputs of the aerogel PENG. 67–69 The output performance of the anisotropic aerogel-based PENG was also measured by applying force along the transverse direction. The nanogenerator delivered an open-circuit voltage of ∼10.5 V and a short circuit current of ∼54 nA along the transverse direction, which is less than the freezing direction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Due to restrictions on the volume and surface area of the fibers, the electrical output of fiber-based TENGs is not high. Therefore, fabric-based TENGs have become an inevitable choice [13][14][15][16][17]. Chen et al [13] also studied the electrical output performance of three basic weaving patterns (plain, sitting, and twill) and reported that the plain pattern had the highest effective illumination area ratio of 96.1%, which delivered the highest current density of 6.35 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%